Pengembangan Model Projec Based Learning (PjBL) Berwawasan Lingkungan sebagai Upaya Meningkatkan Kemampuan Berpikir Kritis pada Siswa Sekolah Dasar (SD): Development of an Environmentally-Based Project-Based Learning (PjBL) Model as an Effort to Enhance Critical Thinking Skills in Elementary School Students - Azis, Hendra Sidratul Azis (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Effective education in the era of globalization not only emphasizes knowledge mastery but also the critical thinking skills of students, especially in addressing environmental issues. Environmentally oriented Project-Based Learning (PjBL) is an innovative approach that can enhance students' critical thinking and collaboration skills, as well as increase their awareness of environmental problems. This study aims to develop and implement a project-based learning model focused on environmental issues at the elementary school level. The method used is Research and Development (R&D), which consists of needs analysis, design, product development, testing, and implementation. This model engages students in real-world projects that address environmental issues, such as waste management and nature conservation, with the aim of improving knowledge, critical thinking skills, and collaboration among students. The results show a significant improvement in students' knowledge about environmental issues, problem-solving skills, and collaboration. Furthermore, this model successfully provided positive impacts on the surrounding environment, such as improved waste management at the school and environmental campaigns in the community. Overall, the implementation of this project-based learning model proved effective in achieving educational goals, namely enhancing students' knowledge, critical thinking skills, and environmental awareness. Keywords: Project-based learning, critical thinking skills, environmental awareness